Genomic evidence of neo-sex chromosomes in the eastern yellow robin - Gan, Han Ming (Gigascience, 2019)
BACKGROUND: Understanding sex-biased natural selection can be enhanced by access to well-annotated chromosomes including ones inherited in sex-specific fashion. The eastern yellow robin (EYR) is an endemic Australian songbird inferred to have experienced climate-driven sex-biased selection and is a prominent model for studying mitochondrial-nuclear interactions in the wild. However, the lack of an EYR reference genome containing both sex chromosomes (in birds, a female bearing Z and W chromosomes) limits efforts to understand the mechanisms of these processes. Here, we assemble the genome for a female EYR and use low-depth (10×) genome resequencing data from 19 individuals of known sex to identify chromosome fragments with sex-specific inheritance. FINDINGS: MaSuRCA hybrid assembly using Nanopore and Illumina reads generated a 1.22-Gb EYR genome in 20,702 scaffolds (94.2% BUSCO completeness). Scaffolds were tested for W-linked (female-only) inheritance using a k-mer approach, and for Z-linked inheritance using median read-depth test in male and female reads (read-depths must indicate haploid female and diploid male representation). This resulted in 2,372 W-linked scaffolds (total length: 97,872,282 bp, N50: 81,931 bp) and 586 Z-linked scaffolds (total length: 121,817,358 bp, N50: 551,641 bp). Anchoring of the sex-linked EYR scaffolds to the reference genome of a female zebra finch revealed 2 categories of sex-linked genomic regions. First, 653 W-linked scaffolds (25.7 Mb) were anchored to the W sex chromosome and 215 Z-linked scaffolds (74.4 Mb) to the Z. Second, 1,138 W-linked scaffolds (70.9 Mb) and 179 Z-linked scaffolds (51.0 Mb) were anchored to a large section (coordinates ∼5 to ∼60 Mb) of zebra finch chromosome 1A. The first ∼5 Mb and last ∼14 Mb of the reference chromosome 1A had only autosomally behaving EYR scaffolds mapping to them. CONCLUSIONS: We report a female (W chromosome–containing) EYR genome and provide genomic evidence for a neo-sex (neo-W and neo-Z) chromosome system in the EYR, involving most of a large chromosome (1A) previously only reported to be autosomal in passerines.